The Effect of Organizational Commitment, Work Discipline and Locus of Control on the Performance of Employees of the Production Department of PT. Nusantara Beta Farma Padang Pariaman - Yulihardi, Yulihardi; Rina Febriani,; Tiara Kurnia Sari; Budiyanto, Budiyanto; Agus Tedi (Adpebi Science Series, 2024)
Human resources are an important factor that cannot be separated from an organization or company.Human resources are also the key to determining the development of an organization and act as drivers, thinkersand planners to achieve organizational goals, so companies must pay attention to the performance of allemployees. This research aims to determine the influence of organizational commitment, work discipline andlocus of control on employee performance in the production section of PT. Nusantara Beta Farma PadangPariaman. This research uses associative research. The population and sample in this research were allemployees in the production department of PT. Nusantara Beta Farma Padang Pariaman, totaling 67 employeeswith a sampling technique using Non-Propability Sampling, namely a saturated sampling technique. Datacollection techniques use questionnaires.Based on the SPSS calculation results from the t test, the Organizational Commitment variable tcount >ttable or 2.266 > 1.669 (sig = 0.027 < 0.05) means that H1 is accepted and H0 is rejected. So it can be concludedthat Organizational Commitment has a positive and significant effect on Employee Performance at PT. NusantaraBeta Farma Padang Pariaman. In the Work Discipline variable tcount > ttable or 6.070 > 1.669 (sig = 0.000 <0.05) meaning that H2 is accepted and H0 is rejected. So it can be concluded that the Work Discipline variablehas a positive and significant effect on employee performance. In the Locus of Control, variable tcount > ttableor 2.170 > 1.669 (sig = 0.034 < 0.05) meaning that H3 is accepted and H0 is rejected. So it can be concludedthat the Locus of Control variable has a positive and significant effect on employee performance.The results of the f test show that if fcount > ftable then H4 is accepted and H0 is rejected and vice versaif fcount < ftable then H4 is rejected and H0 is accepted. Based on table 4.15 of the f test, it is known that thefcount value is 25,483 and the ftable value is 2,751 so that H4 is accepted and H0 is rejected with a significantvalue of 0.000 (<0.05). This means that together the variables Organizational Commitment, Work Discipline andLocus of Control influence the employee performance of PT. Nusantara Beta Farma Padang Pariaman.The R-square value is 0.548, meaning that the percentage influence of Organizational Commitment,Work Discipline and Locus of Control on PT. Nusantara Beta Farma Padang Pariaman Employee Performanceis 54.8% while the remaining 45.2% is influenced by other variables not examined in this research. So it can beconcluded that Organizational Commitment, Work Discipline and Locus of Control influence the Performance ofEmployees in the Production Department of PT. Nusantara Beta Farma Padang Pariaman